2011
DOI: 10.1180/minmag.2011.075.6.2755
|View full text |Cite
|
Sign up to set email alerts
|

From structure topology to chemical composition. XII. Titanium silicates: the crystal chemistry of rinkite, Na2Ca4REETi(Si2O7)2OF3

Abstract: Rinkite, ideally Na2Ca4REETi(Si2O7)2OF3, is a common mineral in alkaline and peralkaline rocks. The crystal structures of five rinkite crystals from three alkaline massifs: Ilimaussaq, Greenland; Khibiny, Kola Peninsula, Russia and Mont Saint-Hilaire, Canada, have been refined as two components related by the TWIN matrix (–1 0 0, 0 –1 0, 1 0 1) (Mo-αa radiation). The crystals, a = 7.4132-7.4414, b = 5.6595-5.6816, c = 18.8181-18.9431 Å, β = 101.353-101.424(2)°, V= 776.1-786.7 Å3, space group P21lc, Z = 2, Dcal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
23
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 26 publications
1
23
0
1
Order By: Relevance
“…Following Cámara et al (2011), we have fitted the data reported here along with those presented by them REE + Y contents in our nacareniobsite-(Ce) vary between 21.1 and 24.9 wt.% (1.08-1.28 apfu) and are, in general, higher than literature data (cf. Table 3).…”
Section: The a P M Omentioning
confidence: 55%
See 3 more Smart Citations
“…Following Cámara et al (2011), we have fitted the data reported here along with those presented by them REE + Y contents in our nacareniobsite-(Ce) vary between 21.1 and 24.9 wt.% (1.08-1.28 apfu) and are, in general, higher than literature data (cf. Table 3).…”
Section: The a P M Omentioning
confidence: 55%
“…Structural formulae were computed on the basis of 18 (O + F) for nacareniobsite-(Ce) and 26 (O,F) for britholite-(Ce), following Cámara et al (2011) and Oberti et al (2001), respectively.…”
Section: Electron Probe Microanalysesmentioning
confidence: 99%
See 2 more Smart Citations
“…Rinkite [ideally Na 2 Ca 4 REETi(Si 2 O 7 ) 2 OF 3 ; Camara et al (2011) ], occurs as long (~5-10 × 50-200 μm) needle-like prismatic crystals ( Fig. 6) with the altered eudialyte aggregates.…”
Section: Rinkitementioning
confidence: 99%